(untitled) (Bangabandhu Sheikh Mujib Medical University Journal, 2016)
Background: Cerebral palsy (CP) is a major cause of crippling in children. Several antenatal, natal and post natal factors for CP like birth asphyxia and pretenn & LBW deliveries were identified. Objective: To see the presence of known risk factors of CP and co-morbidities in our setting. Methods: ln this study 100 cases of cerebral palsy attending the child neurology out-patient department Bangabandhu Sheikh Mujib Medical University (BSMMU) were evaluated with special attention to risk factors of CP. Full evaluation was done to find out co-morbidities. Results: Birth asphyxia (49%) was the most common risk factor. Mental retardation; speech problem and seizure were common co-morbidities. Conclusion: As birth asphyxia is common risk factor of cerebral palsy, it may be reduced by improving perinatal care.